NILAI SOSIAL DALAM CERPEN “NYANYIAN MALAM” KARYA AHMAD TOHARI: PENDEKATAN SOSIOLOGI SASTRA - Siti Karomah; Widowati; Sindy Febrianisa (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2025)
The purpose of this study is to analyze and describe the social values ​​contained in the short story "Nyanyian Malam" by Ahmad Tohari so that it can be used as a reference for readers of literature and implemented in the social life of society. The type of research used is a literature study using a descriptive-qualitative approach. The research data are: words, phrases, and sentences related to social values ​​in the short story "Nyanyian Malam" by Ahmad Tohari. The data collection technique is reading and grouping data according to the research object. The data analysis technique is by (1) reading, (2) describing, (3) interpreting, (4) drawing conclusions. The results of this study found 6 types of social values ​​in the short story "Nyanyian Malam", namely: helping each other found 6 data, empathy found 4 data, loyalty found 1 data, caring found 1 data, religiosity found 1 data and politeness found 1 data. These findings indicate that the social values ​​contained in the short story "Nyanyian Malam" greatly influence the relationship between characters, both in the context of family, society, and in the individual's own life.